2002
DOI: 10.1016/s1470-0328(02)02956-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the outcome of early medical abortion: a review of 4132 consecutive cases

Abstract: Objective To assess the outcome of a regimen of a reduced dose of mifepristone followed by one or two doses of vaginal misoprostol as a non-surgical method for termination of pregnancy.Design Prospective observational study.Setting Aberdeen Royal Infirmary, Aberdeen, Scotland.Population Women seeking abortion under the 1967 Abortion Act.Methods Factors influencing the outcome in a consecutive series of 4132 women undergoing early medical abortion in one Scottish teaching hospital since 1994.Main outcome measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 10 publications
(28 reference statements)
2
43
4
Order By: Relevance
“…Although it has previously been shown in a large observational study of over 4000 cases of early medical abortion that addition of a further dose of misoprostol can reduce the ongoing pregnancy rate, we did not find a significant difference in the number of ongoing pregnancies following EMD treatment or day case treatment 14. While we do not know what proportion of women in the day case group received the extra dose of misoprostol, clearly it is reassuring that women in our study who chose EMD (and thus received a single dose of misoprostol only) were not disadvantaged by this.…”
Section: Discussioncontrasting
confidence: 99%
“…Although it has previously been shown in a large observational study of over 4000 cases of early medical abortion that addition of a further dose of misoprostol can reduce the ongoing pregnancy rate, we did not find a significant difference in the number of ongoing pregnancies following EMD treatment or day case treatment 14. While we do not know what proportion of women in the day case group received the extra dose of misoprostol, clearly it is reassuring that women in our study who chose EMD (and thus received a single dose of misoprostol only) were not disadvantaged by this.…”
Section: Discussioncontrasting
confidence: 99%
“…In concordance with previous research, we have shown that both previous termination and increasing gestation are factors associated with failure of EMA 16 17. Previous studies have reported that EMA failure rate and subsequent requirement for surgical intervention was higher in women who were parous compared with those who were nulliparous 16. In the present study, we have not shown any significant association between parity and success of EMA.…”
Section: Discussioncontrasting
confidence: 73%
“…12,17 These findings may be useful in counselling women undergoing medical abortion in home settings. However, analgesia requirements will need to be evaluated in different settings and preferably in the context of a randomised trial.…”
Section: Discussionmentioning
confidence: 95%
“…[10][11][12][13][14][15][16] Caution, nonetheless, is essential in advising women about undergoing medical abortion at home. Ensuring that women live within a reasonable distance of the hospital remains important at this stage until more safety data become available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation